2020
DOI: 10.21315/mjms2020.27.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic and Insulin Secretagogue Activities of (R)-(−)-Carvone

Abstract: Background: Dyslipidaemias are common in patients with diabetes mellitus. A high prevalence of type 2 diabetes in hyperlipidaemic patients also exists. The aim of this study was to find a treatment that lowers both blood glucose and lipid levels simultaneously. Methods: The hypolipidaemic effect of (R)-(−)-carvone was investigated in a tyloxapol- induced hyperlipidaemia mice model. Furthermore, its effect on insulin secretion and proliferation of 1.1E7 human pancreatic β-cells was studied. In addition, using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Following a one-month intervention with carvone, metformin, and atorvastatin, we saw a decrease in blood glucose levels. We also observed a decrease in lipid profile [25] in another study that showed that carvone has hypolipidaemic properties which come in the same line of our result . Plasma cholesterol levels and atherosclerosis have an undeniable causal link.…”
Section: Discussionsupporting
confidence: 91%
“…Following a one-month intervention with carvone, metformin, and atorvastatin, we saw a decrease in blood glucose levels. We also observed a decrease in lipid profile [25] in another study that showed that carvone has hypolipidaemic properties which come in the same line of our result . Plasma cholesterol levels and atherosclerosis have an undeniable causal link.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained in this study suggest that (R)-(-)-carvone may be useful by targeting the interaction between inflammatory and anti-inflammatory/antioxidant signaling pathways and intermediates. Interestingly, some recent in vivo studies reported interesting activities of (R)-(-)-carvone, namely hypolipidaemic and insulin secretagogue activities [ 38 ], protection from doxorubicin-induced cardiotoxicity [ 39 ] and anti-allergic airway inflammation [ 40 ]. Although the molecular mechanisms underlying these activities were not clearly elucidated, the ability of (R)-(-)-carvone to activate Nrf2 and inhibit NF-κB may be especially relevant since all these conditions are associated with oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms underlying these activities were not clearly elucidated, the ability of (R)-(-)-carvone to activate Nrf2 and inhibit NF-κB may be especially relevant since all these conditions are associated with oxidative stress and inflammation. In one of these studies, for instance, (R)-(-)-carvone decreased catalase activity in the liver of hyperlipidaemic mice [ 38 ]. Since catalase is an antioxidant enzyme whose expression is induced by Nrf2 [ 41 ], it can be speculated that activation of this transcription factor by (R)-(-)-carvone is a relevant mechanism underlying its beneficial effects in hyperlipidemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described that carvone and carveol can produce a significant decrease in triglycerides (TG), total cholesterol (TC) and low-density lipoprotein (LDL) and a significant increase in high-density lipoprotein (HDL), suggesting anti-hyperlipidemic properties. 107,115 Furthermore, carvone decreased atherogenic index and increased proliferation and insulin secretion of human pancreatic β-cells.…”
Section: Anethum Graveolens Essential Oilmentioning
confidence: 98%